Paediatric Musculoskeletal Disease With an Emphasis on Ultrasound - Wilson, David J. (Diagnostic Imaging, 2005)
Ultrasound is a technique particularly suited to the investigation of disorders in children. It is painless, safe and non-threatening. There are significant strengths and weaknesses of its use in the diagnosis of musculoskeletal disorders. This text describes the methods, findings and potential pitfalls of imaging where US is commonly used as the primary diagnostic method and where it is best as an adjunct to other imaging. The alternative imaging techniques including CT, MRI, scintigraphy and plain radiography are described in detail where appropriate. The reader of this book should obtain a working knowledge of the potential advantages of US whilst understanding when and where other forms of imaging are preferred. The authors have international reputations as researchers, clinicians and teachers in their field.